2020
DOI: 10.1590/2175-7860202071110
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic analyses and genomic affinity among Argentinean species of Passiflora

Abstract: The genus Passiflora (Passifloraceae) has more than 500 species, nineteen are native to Argentina. By their austral distribution, these species were included in breeding programs to obtain ornamental varieties tolerant to low temperatures. The aim of this work was to know the cytogenetic characteristics of Passiflora genotypes present in a working collection, as an indispensable knowledge for the development of a breeding plan. Chromosomal preparations were performed and karyotypic characteristics, rDNA sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…This similarity in genome size between both subgenera is in coincidence with an evolutionary closeness, supported by karyotype analysis and in the haploid chromosome length (HCL) and karyotypical symmetry indices. Nonetheless, results of GISH analysis showed that there is greater homology between the genomes of the Passiflora and Dysosmia subgenera (Bugallo et al 2020), agreeing with the molecular phylogenies of Muschner et al (2003) and Sader et al (2019). However, the hypothesis made by Sader et al (2019), asserting that the species of the subgenus Dysosmia derives from the subgenus Passiflora also assumes that there would be an intermediary between the subgenera Decaloba and Passiflora with a basic number x = 8, an unknown number within species of the genus.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…This similarity in genome size between both subgenera is in coincidence with an evolutionary closeness, supported by karyotype analysis and in the haploid chromosome length (HCL) and karyotypical symmetry indices. Nonetheless, results of GISH analysis showed that there is greater homology between the genomes of the Passiflora and Dysosmia subgenera (Bugallo et al 2020), agreeing with the molecular phylogenies of Muschner et al (2003) and Sader et al (2019). However, the hypothesis made by Sader et al (2019), asserting that the species of the subgenus Dysosmia derives from the subgenus Passiflora also assumes that there would be an intermediary between the subgenera Decaloba and Passiflora with a basic number x = 8, an unknown number within species of the genus.…”
Section: Discussionmentioning
confidence: 66%
“…A linear regression was performed between the total length of the genome, estimated by measuring the chromosomes in the genotypes of the collection (Bugallo et al 2020), and the amount of DNA per haploid genome estimated in this work. The results showed that the two variables were closely correlated, with a coefficient of determination R 2 = 0.95 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations